The U.K. Treasury Infrastructure Finance Unit : Supporting PPP Financing During the Global Liquidity Crisis - Farquharson, Ed; Encinas, Javier (World Bank, Washington, DC, 2015)
2008 and 2009 were challenging years to raise finance for public-private partnerships (PPP) and private finance initiative (PFI) schemes in the United Kingdom (UK). After some analysis, it was decided to focus on addressing the underlying problem of liquidity and to provide a solution that will encourage banks to resume their long-term financing of projects. In March 2009, the treasury created the infrastructure finance unit (TIFU) with the objective of lending to PFI projects on the same terms as commercial lenders in the event that insufficient private sector lending was available. This was successful in helping to inject confidence back into the market, as witnessed by the fact that projects have continued to be financed since the onset of the credit crisis. Recently, Her Majesty (HM) treasury announced that it will bring together of TIFU, the program and project delivery team of partnerships UK, and the treasury PPP policy unit into a single entity, infrastructure UK (IUK), which will focus on the next stage of U.K. infrastructure development.